Cardiopulmonary adaptation to short-term high altitude exposure in adult Fontan patients. Issue 16 (23rd May 2016) - Staempfli, Roger; Schmid, Jean-Paul; Schenker, Stephan; Eser, Prisca; Trachsel, Lukas D; Deluigi, Christina; Wustmann, Kerstin; Thomet, Corina; Greutmann, Matthias; Tobler, Daniel; Stambach, Dominik; Wilhelm, Matthias; et al.
Abstract : Objective: High altitude-related hypoxia induces pulmonary vasoconstriction. In Fontan patients without a contractile subpulmonary ventricle, an increase in pulmonary artery pressure is expected to decrease circulatory output and reduce exercise capacity. This study investigates the direct effects of short-term high altitude exposure on pulmonary blood flow (PBF) and exercise capacity in Fontan patients. Methods: 16 adult Fontan patients (mean age 28±7 years, 56% female) and 14 matched controls underwent cardiopulmonary exercise testing with measurement of PBF with a gas rebreathing system at 540 m (low altitude) and at 3454 m (high altitude) within 12 weeks. Results: PBF at rest and at exercise was higher in controls than in Fontan patients, both at low and high altitude. PBF increased twofold in Fontan patients and 2.8-fold in the control group during submaximal exercise, with no significant difference between low and high altitude (p=0.290). A reduction in peak oxygen uptake at high compared with low altitude was observed in Fontan patients (22.8±5.1 and 20.5±3.8 mL/min/kg, p<0.001) and the control group (35.0±7.4 and 29.1±6.5 mL/min/kg, p<0.001). The reduction in exercise capacity was less pronounced in Fontan patients compared with controls (9±12% vs 17±8%, p=0.005). No major adverse clinical event was observed. Conclusions: Short-term high altitude exposure has no negative impact on PBF and exercise capacity in Fontan patients when compared with controls, and was clinically well tolerated. Trial registration number: NCT02237274: Results.